Total tardiness problem with future job arrival information - Huang, Fengjie (2014)
We consider a single machine total tardiness problem with different release times, different due dates and available information of future job arrival in the next time period W. The goal is to generate an effective schedule for minimizing total tardiness by utilizing the future job information.